EFEKTIVITAS PENGETAHUAN ORANGTUA BATITA TERHADAP KETEPATAN IMUNISASI DASAR DAN BOOSTER PADA MASA PANDEMI COVID-19 DI POSYANDU WILAYAH KERJA PUSKESMAS COLOMADU - Yeni Anggraini; Kurnia Agustin (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2020)
ABSTRACT One of the things that highlighted during the Covid-19 pandemic at many integrated service post of Primary Health Care was closed immunization services for childrens under five years old. This means that the basic immunization coverage for childrens under five years old will be even smaller in the midst of the current Covid pandemic (Utami, 2020). However, during the COVID-19 pandemic, immunization must be completed according to schedule to protect children from PD3I (Ministry, 2020). This study aims to analyze the effectiveness of parental knowledge of childrens under three years old on the accuracy of basic and booster immunizations during the COVID-19 pandemic. This type of research is observational analytic. The sample presentation technique used is